Outcomes in Adult Liver Transplant Recipients Using Pediatric Deceased Donor Liver Grafts. Issue 5 (7th April 2022) - Vargas, Paola A.; Wang, Haowei; Dalzell, Christina; Argo, Curtis; Henry, Zachary; Su, Feng; Stotts, Matthew J.; Northup, Patrick; Oberholzer, Jose; Pelletier, Shawn; Goldaracena, Nicolas
Abstract : Background: The use of pediatric grafts for liver transplantation (LT) into adult recipients is rare, and reported outcomes are conflicting. The aim of this study is to evaluate the outcomes in adult recipients following LT with grafts from deceased pediatric donors. Methods: A retrospective study identifying adult LT between 2010 and 2020 using pediatric deceased donor liver grafts was conducted. Adults undergoing LT with deceased donor pediatric grafts (age ≤ 12) were identified and matched 1:2 with adults receiving adult grafts (age ≥ 18) based on recipient age (±10 y), model for end-stage liver disease (MELD) score at transplant (±5 points) and etiology of liver disease. To assess real liver size differences between the pediatric-donor and adult-donor groups, patients receiving a graft from a donor between 13 and 17 y were excluded from the main analysis and studied independently. Outcomes between the groups were compared. Complication rates were identified and graded using Clavien–Dindo classification. Graft and patient survival were assessed by Kaplan–Meier curves. Results: Twelve adult LT recipients with whole liver grafts from deceased pediatric donors were matched with 24 adult recipients of adult donors. Recipient age and MELD score were similar between groups. Recipients of pediatric grafts were more likely to be female (66.7% versus 16.7%, P = 0.007) and leaner (body mass index = 24.4 versus 29.9, P = 0.013). Alcohol-related cirrhosis was the most prevalent liver disease etiology in both groups ( P = 0.96). There was no significant difference in length of stay, readmissions, early complications, or major complications between groups. Vascular and biliary complication rates were similar. Actuarial graft and patient survival at 1, 3, and 5 y were 100/100/100 versus 96/96/96 ( P = 0.48). Conclusions: Excellent patient and graft survival is achievable with LT using young pediatric deceased donor grafts in smaller adult recipients. Outcomes are comparable with recipients of age and MELD-matched adult donors. Careful donor MELD-score recipient matching and close monitoring for potential biliary and vascular complications are crucial to achieve acceptable outcomes.